Characteristics of Secondary PM2.5 Under Different Photochemical Reactivity Backgrounds in the Pearl River Delta Region - Yu, Xinyang; Zhang, Yin; Liu, Ningwei; Yang, Suying (Frontiers in Environmental Science, 2022)
With the control of air pollution, the levels of atmospheric particulate in the Pearl River Delta region (PRD) are gradually decreasing. However, ozone pollution becomes more and more serious, and the problem of secondary aerosol pollution caused by photochemical reactions cannot be ignored. Based on the observation data of environmental and meteorological stations in the nine cities of PRD during 2019, we investigated the variations of secondary PM2.5 (PM2.5-sec) in PRD under different photochemical reactivity backgrounds. It is shown that the photochemical reactivities appear more significant in the central and western areas than in the eastern areas of PRD, and appear more significant in inland areas than in coastal areas. The days of moderate and high photochemical reactivities mainly appear from August to November. PM2.5-sec concentrations are the highest in autumn, during which the regional discrepancies appear the most significantly with the highest levels in the south areas. With the enhancement of photochemical reactivity background, the PM2.5-sec level at each station increases significantly, which appears significantly higher in coastal areas than in inland areas. Both PM2.5-sec and ozone concentrations shows single-peak variations, which appear higher in the daytime than at night with the peak occurs at about 15:00. As for each pollutant, the average maximum concentration appears higher for polluted stations than for clean ones, indicating that atmospheric oxidation background is conducive to the formation of PM2.5-sec.